Prediction of chemotherapy outcome in patients with metastatic soft tissue sarcomas based on dynamic FDG PET (dPET) and a multiparameter analysis - Dimitrakopoulou-Strauss, Antonia; Strauss, Ludwig G.; Egerer, Gerlinde; Vasamiliette, Julie Sigrid Lucienne; Schmitt, Thomas; Haberkorn, Uwe; Kasper, Bernd (European journal of nuclear medicine and molecular imaging, 2010)
Dynamic PET studies with 18F-FDG were performed in patients with metastatic soft tissue sarcomas who received conventional chemotherapy with doxorubicin hydrochloride (Adriamycin) and ifosfamide (AI-G). The goal of the study was to evaluate the impact of full kinetic analysis and assess its value with regard to the therapy outcome based on survival data.